Analisis Hubungan Ketimpangan Regional Di Indonesia : Sebelum Dan Setelah Pandemi - Bagus Muldiansyah; Muhammad Irfan (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to analyze the level of regional and human development inequality between provinces in Indonesia and examine the relationship between the two before, during, and after the COVID-19 pandemic. The variables used include per capita income (GRDP), education (average years of schooling), unemployment (open unemployment rate), and health (percentage of the population with health complaints). This study uses secondary data from the (BPS) covering 34 provinces in 2015, 2020, and 2024. The analytical method used is descriptive analysis with the Coefficient of Variation (CV) to measure the level of inequality, as well as inferential analysis using the Wilcoxon Signed Rank Test and correlation analysis. The results show that regional development inequality in terms of income tends to decrease relatively. Human development inequality in education indicators shows a decline, indicating equity, while inequality in health indicators tends to increase, and inequality in unemployment decreases with the post-pandemic economic recovery. Inferential test results show significant differences before and after the pandemic, as well as a relationship between income inequality and human development. This study concludes that the pandemic has had a different impact on each dimension of inequality, necessitating more inclusive and equitable development policies to reduce disparities between regions in Indonesia.